2021
DOI: 10.1002/cam4.4395
|View full text |Cite
|
Sign up to set email alerts
|

The roles of ferroptosis regulatory gene SLC7A11 in renal cell carcinoma: A multi‐omics study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Intriguingly, the ferroptosis driver and marker, TFRC was downregulated in SLC1A5-silencing tumors, whereas the ferroptosis suppressor SLC7A11 also appeared the same tendency. One possible reason was that Fe ion and cystine that relied on TFRC and SLC7A11 transport were essential for tumor growth ( Thévenod 2018 ; Xu et al, 2021a ; Koppula et al, 2021 ). Briefly, targeting SLC1A5 showed promising potentials in PC treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the ferroptosis driver and marker, TFRC was downregulated in SLC1A5-silencing tumors, whereas the ferroptosis suppressor SLC7A11 also appeared the same tendency. One possible reason was that Fe ion and cystine that relied on TFRC and SLC7A11 transport were essential for tumor growth ( Thévenod 2018 ; Xu et al, 2021a ; Koppula et al, 2021 ). Briefly, targeting SLC1A5 showed promising potentials in PC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, NCOA4, a ferritinophagy regulatory gene, leads to unfavorable prognosis and defective immune cell infiltration in renal cancer ( Mou et al, 2021 ). SLC7A11, a cystine/glutamate antiporter, not only enhances cervical cancer progression by circEPSTI1-miR-375-SLC7A11 axis ( Wu et al, 2021 ) but also serves as an unfavorable prognostic biomarker in renal carcinoma ( Xu et al, 2021a ). Alternatively, SLC1A5 has been identified as a positive modulator of ferroptosis ( Cao and Dixon 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, several studies have reported that the regulation of FRGs can affect the process and the prognosis of ccRCC (33,34). But to our knowledge, there are still not enough studies on the correlation of FRGs with the prognosis and the treatment of ccRCC patients, and most of these studies only focus on a single FRG (18,19). Therefore, constructing an FRGs-based, accurate stratified model to allow for prognosis and treatment stratification of ccRCC patients will have important clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lot of details between FRGs and ccRCC patients remain unknown. Most studies focus on a single gene such as SLC7A11 and PRAS40 (18,19). Therefore, there is an urgent need to develop a ccRCC patient stratified model based on FRGs to measure the prognosis and treatment sensitivity, so as to help timely intervention and individualized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an innovative NRF2 nano-modulator induces lung cancer ferroptosis and elicits an immunostimulatory tumor microenvironment 13 . SLC7A11 promoted the proliferation, migration, and invasion of renal cancer cells by enhancing GPX4 output, which in turn inhibits ferroptosis 14 . Therefore, targeting ferroptosis may be a new strategy for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%